Multi-level ecological restoration zoning in Sanmenxia City: A patterns-ecosystems-humans perspective - Guangjin Zhou; Yizhong Huan; Qijia Lou; Tao Liang; Zhiguang Shi; Xiaoman Liu; Siyuan Tao; Riqi Zhang; Jixi Gao; Yiping Zuo (Ecological Informatics, 2025)
Ecological restoration zoning is a critical component of ecological restoration planning, providing spatial guidance for the layout of restoration projects. However, no consensus on a standardized technical process for ecological restoration zoning has been reached. This study proposes a multi-level ecological restoration zoning framework from a “patterns-ecosystems-humans” perspective to offer differentiated and targeted guidance. First-level zones were initially delineated based on the natural geographical pattern and the provincial ecological restoration zoning plan. Subsequently, second-level zones were identified using various quantitative models and machine learning methods to define dominant ESs and key ecological challenges. Finally, the second-level zones were further subdivided into third-level zones based on the degree of human interference. This framework was applied in a case study of Sanmenxia City, delineating 3 first-level zones, 12 seconds-level zones, and 3 third-level zones, including ecological conservation zones, key restoration zones, and general restoration zones. Ecological conservation and key restoration zones accounted for 40.84 % and 29.93 % of the city's area, respectively. According to the ecosystem service index proposed in this study, five ecological restoration zones in Sanmenxia City exhibit significant multifunctionality, encompassing 53.3 % of the city's area. Overall, this study presents a clear and practical paradigm for ecological restoration zoning that aligns with provincial spatial ecological protection patterns while effectively guiding differentiated restoration efforts. This framework offers a valuable reference for ecological restoration in China's urban scale.